The effectiveness of content based on dynamic intellectual learning with visual modality in vocational school - Ketut Agustini; I Gede Parta Sindu; Kadek Angga Kusuma (Jurnal Pendidikan Vokasi, 2019)
E-learning generally presented the same learning material because it considered the characteristics of all users to be homogeneous. In fact, every student had different characteristics in the learning process. The objectives of this study were: (1) To produce a simulation content and digital communication based on  Dynamic Intellectual Learning with Visual Modality for the tenth grade at SMK Negeri 1 Seririt, (2) To find out the teacher's response and the tenth grade students at SMK Negeri 1 Seririt on Simulation Content and Digital Communication based on DIL with Visual Modality that had been generated. The method of this study was a research and development referred to the plomp model. The subjects of this study were the tenth grade of accounting program at SMK Negeri 1 Seririt in the academic year 2017/2018. There were various try out had been carried out, namely: validity testing by experts and effectiveness testing by using the Hake formula. The results showed that the simulation content and digital communication based on DIL with Visual Modality was valid and practically use: the effectiveness testing produced N-gain of 0.74 included in the effective category and the data analysis of the teacher and the students respond showed that it was categorized in the positive category. It showed that the output was valid, practical and effective to be used.